Social Innovation in Chile: A View from the Company (GESTIÓN Y TENDENCIAS, 2019)
Faced with the growing complexity of the social and sustainability problems of modern society, various social innovations have emerged to generate solutions to problems not effectively addressed by the political-administrative and economic system. This effort has arisen especially from civil society, represented largely by non-governmental organizations. The business world has not been a stranger to this effort, and its interest in contributing to social development is increasingly becoming apparent. Given the above, this article seeks to analyze the development of social innovation in companies in Chile, referring to the concept and describing the current situation.